Activated carbon adsorption behaviour of toluene at various temperatures and relative humidity - Görgülü, Adnan; Yağli, Hüseyin; Koç, Yildiz; Koç, Ali; Baltacıoğlu, Ertuğrul (Oficyna Wydawnicza Politechniki Wrocławskiej, 2019)
Filtration plays a major role in managing the rapid increase of environmental pollution and deterioration of atmospheric air quality. One of the most damaging noxious gases in the atmosphere is toluene, which is a common gas that appears in crude oil and is used in various production processes. The adsorption behaviour of activated carbon was examined in dependence of the concentration, temperaturę and relative humidity. The results showed that increasing air temperature decreased the time to reach the maximum saturation ratio, which occurred due to the increasing pore diffusion coefficient and pore diffusion rate.
Environment Protection Engineering. Vol. 45, 2019, nr 1, s. 111-126
Keywords: ochrona środowiska; inżynieria środowiska